The Politics of Vulnerability in Refugee Admissions Under the EU-Turkey Statement - Welfens, Natalie; Bekyol, Yasemin (Frontiers in Political Science, 2021)
Resettlement and humanitarian admission programs claim to target ‘particularly vulnerable’, or ‘the most vulnerable’ refugees. If the limited spots of such programs are indeed foreseen for particularly vulnerable groups and individuals, as resettlement actors claim, how is vulnerability defined in policies and put into practice at the frontline? Taking European states’ recent admission programs under the EU-Turkey statement as an example, and focusing on Germany as an admission country, this research note sheds light on this question. Drawing on document analysis, and original fieldwork insights, we show that on paper and in practice vulnerability as a policy category designates some social groups as per se more vulnerable than others, rather than accounting for contingent reasons of vulnerability. In policy documents, the operational definition of vulnerability and its relation to other criteria remain largely undefined. In selection practices, additional criteria curtail a purely vulnerability-based selection, exacerbate existing or create new vulnerabilities in their own right. We conclude that, in the absence of clear definitions, resettlement and humanitarian admission programs’ declared focus on the most vulnerable remains a discretionary promise, with limited possibilities of political and legal scrutiny.